2014
DOI: 10.1016/j.physbeh.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and metabolic consequences of scheduled consumption of large, binge-type meals of high fat diet in the Sprague–Dawley rat

Abstract: Providing rats and mice with access to palatable high fat diets for a short period each day induces the consumption of substantial binge-like meals. Temporal food intake structure (assessed using the TSE PhenoMaster/LabMaster system) and metabolic outcomes (oral glucose tolerance tests [oGTTs], and dark phase glucose and insulin profiles) were examined in Sprague–Dawley rats given access to 60% high fat diet on one of 3 different feeding regimes: ad libitum access (HF), daily 2 h-scheduled access from 6 to 8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
42
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 26 publications
13
42
1
2
Order By: Relevance
“…Schedule-fed mice showed a large reduction in control diet intake during the early hours of the dark phase and in the hours following the scheduled feed. However, notably, and in line with our previous observations in rats (Bake et al., 2014), schedule-fed mice did not significantly reduce their control diet intake when analysed in 1 h intervals (Fig. 2A,C,F) or change their meal pattern (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Schedule-fed mice showed a large reduction in control diet intake during the early hours of the dark phase and in the hours following the scheduled feed. However, notably, and in line with our previous observations in rats (Bake et al., 2014), schedule-fed mice did not significantly reduce their control diet intake when analysed in 1 h intervals (Fig. 2A,C,F) or change their meal pattern (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…However, the period immediately before scheduled feeding is characterised by near normal levels of caloric intake from stock diet. We have previously observed the same phenomenon in schedule-fed rats (Bake et al., 2014). The absence of relative negative energy balance, in advance of the initiation of the binge, in either species, is in line with our previous findings (Bake et al., 2013) where there was no evidence of potentially causative perturbation in expression of hypothalamic homeostatic neuropeptide genes prior to consumption of large binge-type meals.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Different schedules of diet presentation for the induction of BE-like condition are reported. Daily [18,33,34] or even alternate day [35,36] access to palatable diet for 2-h has been shown to produce BE in rats. However, it is suggested that development of binging is enhanced and remain stable for longer period when it is offered only 3 times per week than for 2-h each day [19,35].…”
Section: Discussionmentioning
confidence: 99%